2017
DOI: 10.1080/10401334.2017.1386106
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Student-Initiated Test Preparation Program for the USMLE Step 1 Examination

Abstract: This study demonstrates the efficacy of a student-initiated curriculum and provides guidance for development and implementation of examination preparatory efforts at other institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…UICOM-Chicago's history of collaboration between students and faculty has resulted in improvements to educational outcomes and student experiences [13]. In this tradition, the SCB was established in 2012 and originally focused on pre-clerkship course program evaluation.…”
Section: The Student Curricular Boardmentioning
confidence: 99%
“…UICOM-Chicago's history of collaboration between students and faculty has resulted in improvements to educational outcomes and student experiences [13]. In this tradition, the SCB was established in 2012 and originally focused on pre-clerkship course program evaluation.…”
Section: The Student Curricular Boardmentioning
confidence: 99%
“…These approaches are excellent at covering large amounts of information and preparing medical students for the complex challenges of clinical medicine, but they are not necessarily structured to help students maximize their performance on standardized tests. (Schwartz et al, 2018) In the medical education literature, there are reports of medical student groups that created student-led Step 1 preparation programs. One of those reports involved cohorts of medical students at the University of Michigan Medical School that took Step 1 in 2014 and 2015, which showed that those who participated achieved higher scores, and they attributed their success to the higher number of practice questions they worked on and their increased usage of review books.…”
Section: Usmle Step 1 Exam Preparation: Current Literaturementioning
confidence: 99%
“…A thorough search of published literature found only two published research initiatives looking at the effects of peer-led sessions on USMLE Step 1 board scores, and those studies used peers from successive classes, not sameclass peers. 33,34 In addition, systematic reviews of peer-led instruction identified epidemiology and biostatistics concepts as ideal for peer-led instruction, but there were very few initiatives in the published literature related to these concepts. 31 From the available literature, current alternatives to EBM instruction lacked viable and resource-free solutions for universal adoption, lacked collaborative approaches to break down difficult concepts, focused too strongly on individualized topics rather than building a basic foundation in EBM, or lacked reinforcement of material through quizzing and assessments.…”
Section: Introductionmentioning
confidence: 99%